Serum levels of ADAM12‐S: possible association with the initiation and progression of dermal fibrosis and interstitial lung disease in patients with systemic sclerosis. (28th April 2012) - Taniguchi, T.; Asano, Y.; Akamata, K.; Aozasa, N.; Noda, S.; Takahashi, T.; Ichimura, Y.; Toyama, T.; Sumida, H.; Kuwano, Y.; Yanaba, K.; Tada, Y.; et al.
Abstract Background A disintegrin and metalloprotease (ADAM) 12 is one of the metalloproteinase‐type ADAMs and possesses extracellular metalloprotease and cell‐binding functions. ADAM12 is expressed in two alternative forms, such as a membrane‐anchored form (ADAM12‐L) and a short secreted form (ADAM12‐S). Objective To investigate the clinical significance of serum ADAM12‐S levels in systemic sclerosis (SSc). Methods Serum ADAM12‐S levels were determined by a specific enzyme‐linked immunosorbent assay in 61 SSc patients and 18 healthy controls. Results Serum ADAM12‐S levels were significantly increased in diffuse cutaneous SSc (dcSSc) patients than in healthy controls (0.417 ± 0.389 vs. 0.226 ± 0.065 ng/mL; P < 0.05), while being comparable between limited cutaneous SSc (0.282 ± 0.258 ng/mL) and healthy controls. Serum ADAM12‐S levels significantly elevated in dcSSc patients with disease duration of ≤6 years (0.537 ± 0.449 ng/mL, P < 0.05), but not in dcSSc with disease duration of >6 years (0.225 ± 0.049 ng/mL), compared to healthy controls. Furthermore, in dcSSc patients with disease duration of ≤6 years, serum ADAM12‐S levels correlated positively with modified Rodnan total skin thickness score, ground glass score, and serum C‐reactive protein values, while showed inverse correlation with fibrosis score. Conclusion Elevated serum ADAM12‐S levels are associated with elevated serum inflammatory marker, severity of skin fibrosis, and activity of interstitial lung disease in dcSSc, suggesting the possible contribution of ADAM12‐S to the pathological events in this disorder.